Timing of acute decompensated heart failure in patients with heart failure and mildly reduced ejection fraction - Steffen, Henning Johann; Abel, Noah; Lau, Felix; Schmitt, Alexander; Reinhardt, Marielen; Akın, Muharrem; Bertsch, Thomas; Rusnak, Jonas; Weidner, Kathrin; Behnes, Michael; Akın, Ibrahim; Schupp, Tobias (Heart and vessels, 2025)
This study investigates the prognosis of acute decompensated heart failure (ADHF) on admission (i.e., primary ADHF) as compared to ADHF onset during course of hospitalization (i.e., secondary ADHF) in patients hospitalized with heart failure with mildly reduced ejection fraction (HFmrEF). Limited data regarding the prognostic impact of the timing of onset of ADHF is available. Consecutive patients with HFmrEF and ADHF were retrospectively included at one institution from 2016 to 2022. Patients with primary ADHF were compared to patients with secondary ADHF with regard to the primary endpoint all-cause mortality at 30 months. Kaplan-Meier, uni- and multivariable Cox proportional regression analyses were applied for statistics. From a total of 484 patients hospitalized with HFmrEF and ADHF, 67.98% (n = 329) were admitted with primary ADHF. Patients with secondary ADHF had higher rates of concomitant acute myocardial infarction, alongside with a higher extend of coronary artery disease. The risk of all-cause mortality at 30 months was not affected by the timing of ADHF (hazard ratio (HR) = 0.853; 95% confidence interval (CI) 0.653-1.115; p = 0.246). However, patients with primary ADHF were associated with a higher risk of HF-related rehospitalization at 30 months (HR = 2.513; 95% CI 1.555-4.065; p = 0.001), which was still evident after multivariable adjustment (HR = 2.347; 95% CI 1.418-3.883; p = 0.001). The timing of onset of ADHF was not associated with long-term mortality in HFmrEF, however primary ADHF was associated with a higher risk of HF-related rehospitalization.
Online veröffentlicht: 22. Januar 2025
Gesehen am 30.06.2025